PENGEMBANGAN E-LKPD BERBASIS P5 CEGAH ANEMIA DENGAN PANGAN SEHAT SEBAGAI UPAYA DUKUNG CEGAH STUNTING - Sintiani Burhan, Deys; Nusantari, Elya; Solang, Margaretha; S. Kumaji, Syam; Maryati Yusuf, Frida (Universitas Cokroaminoto Palopo, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the Pancasila Student Profile Strengthening Project (P5) with the theme